LA GAMIFICACIÓN COMO ESTRATEGIA DE APRENDIZAJE DE BIOLOGÍA ANIMAL CON LOS ESTUDIANTES DE CUARTO SEMESTRE DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES QUÍMICA Y BIOLOGÍA PERIODO ABRIL-AGOSTO 2020 - Maigua Moyota, Eulalia Jazmín (2020)
Gamification is an essential component for science learning, plays a crucial role in student training; however, its use seems to be unknown by teachers in the career of Pedagogy of Experimental Sciences Chemistry and Biology. Since it has been possible to observe the repetitive use of methodological strategies in the teaching of Animal Biology, it was evident that their learning became tiring and without any meaning. For this reason, it was proposed to analyze gamification as a methodological strategy for the learning of Animal Biology, with the students of the fourth semester of the career of Pedagogy of Experimental Sciences: Chemistry and Biology. The research design was non-experimental, with three types of research: field, bibliographic, and longitudinal, applying the inductive-deductive method and analysissynthesis. When analyzing the results, it was concluded that gamification is of great importance in higher education since 100% of the students affirmed that its application extends their interest and motivation for learning and develops their cognitive abilities. Therefore, it is recommended to extend a comparative study in different subjects and semesters of the career on the utility of gamification as a learning strategy.